Turnaround management - Lenahan, Tom.; ScienceDirect eBooks (Oxford ; Boston, Mass. : Butterworth Heinemann, 1999)
Manufacturing and process plants must be regularly closed down for planned maintenance operations. This may entail the complete shutdown and re-start of large-scale serial and batch operations and must be performed in as short a period of time as is cost-effective. This is the process of turnaround, and as the processes are often high value and the maintenance operations intensive, complex and costly, it is vital that it be planned and carried out effectively. Tom Lenahan is an acknowledged expert in this field, who has worked and consulted internationally, and his book will show the maintenan.
Front Cover; Turnaround management; Copyright Page; Contents; Preface; Foreword; Acknowledgements; Chapter 1. Turnaround overview: context and strategy; Chapter 2. Initiating the turnaround; Chapter 3. Validating the work scope; Chapter 4. Pre-shutdown work; Chapter 5. Contractor packages; Chapter 6. Planning the turnaround; Chapter 7. The turnaround organization; Chapter 8. Site logistics; Chapter 9. The cost profile; Chapter 10. The safety plan; Chapter 11. The quality plan; Chapter 12. The communications package; Chapter 13. Executing the turnaround; Chapter 14. Terminating the turnaround.
Includes index.
Print version record.
Elsevier
Keywords: Project management; TECHNOLOGY & ENGINEERING -- Industrial Technology; TECHNOLOGY & ENGINEERING -- Industrial Engineering; BUSINESS & ECONOMICS -- Production & Operations Management; Project management; Electronic books